The Rule of Law as the Theoretical Basis for State Administrative Law - Guvo Deswarth Purba; Muhyiddin Hilal Sarhan (Program Pascasarjana UIN Sumatera Utara Medan, 2023)
The rule of law is a fundamental principle in governance that places law as the foundation and limit of state power. In the context of state administrative law, the principle of the rule of law plays a crucial role in regulating the implementation of government authority and providing legal protection for citizens. Administrative law is the primary instrument for ensuring that government actions and decisions are implemented based on the principle of legality, general principles of good governance, and effective oversight mechanisms. This study employs a normative legal research method with a statutory and conceptual approach. The legal materials used consist of statutory regulations, expert doctrines, and relevant legal literature. The analysis is descriptive-analytical. The discussion in this journal begins with an elaboration of the concept of the rule of law as the theoretical basis of state administrative law, followed by a discussion of legal protection for citizens and the application of general principles of good governance, as well as the implications of the rule of law for governance. The results of the discussion indicate that the principle of the rule of law plays a crucial role in limiting government power and realizing an orderly, accountable, and just government.